2018
DOI: 10.1108/ilt-06-2016-0130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser surface texturing on tribological properties of polyimide composites in the application of traveling wave rotary ultrasonic motor

Abstract: Purpose The purpose of this paper is to investigate the effect of laser surface texturing on the tribological properties of polyimide composites and the output performance of traveling wave rotary ultrasonic motor. Design/methodology/approach The surface texturing on polyimide composites specimens were fabricated by laser ablation process of different dimple densities, and then the tribological properties were tested by a flat-on-flat tribometer under dry conditions. Finally, the output performance of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the PI composites with a diameter of 0.3 mm and 7.06 per cent area density surface texture have the highest friction coefficient (Liu et al , 2018). Therefore, the surface texture in this experiment also uses the same diameter and area density, radial distribution on the surface of rotor frictional material, as shown in Figure 3.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Previous studies have shown that the PI composites with a diameter of 0.3 mm and 7.06 per cent area density surface texture have the highest friction coefficient (Liu et al , 2018). Therefore, the surface texture in this experiment also uses the same diameter and area density, radial distribution on the surface of rotor frictional material, as shown in Figure 3.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…There are different texturing techniques such as sandblasting, ion beam texturing, etching technique, machining, and laser texturing, being the last one the most innovative in recent years [8,9]. Surface texturing has been used successfully in tribological applications where it is sought to reduce wear between sliding surfaces, since there is evidence that the cavities that are created with this technique can be used to store lubricant (Figure 1(a)) and keep the sliding surfaces constantly lubricated; furthermore, the cavities can also be used to trap wear particles (debris) that would otherwise produce third-body abrasive wear [9][10][11][12], as can be seen in Figure 1 In some cases, the benefits of texturing have been used for biotribological applications with the aim of reducing wear between components of joint prostheses, where positive results have been obtained; an example of this is the work of Ito et al, where concave dimples (diameter of 0.5 mm, pitch of 1.2 mm, and depth of 0.1mm) were textured on the surface of a Co-Cr alloy femoral head using the electrical discharge etching technique. Wear tests were carried out using a hip joint simulator with a metal-on-polyethylene configuration, the results showed that dimples reduced COF and wear by 35% and 68%, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works by researchers has proved that LST can lead to reduction of friction and wear in many tribosystems (Fowell et al , 2012; Gropper et al , 2016; Li et al , 2018; Liu et al , 2018; Wang et al , 2018). Rosenkranz et al (2016) investigated the load-dependent run-in and wear behavior of line-like patterns in tests with stainless steel substrates.…”
Section: Introductionmentioning
confidence: 99%